Y-chromosome haplotypes in East Timor (Timor-Leste): Evidences of population differentiation - Souto, L. (2006)
Haplotype frequencies were determined for 346 individuals from East Timor and 3 major ethnolinguistic groups were compared, putting in evidence the need for detailed analyses below the level of the major ethnolinguistic groups. Search of Timorese haplotypes matches in international databases returns few hits and almost all with Philippine data.